ASPEK-ASPEK DALAM PEMBERIAN OPINI AUDIT GOING CONCERN - SOEWIYANTO, MARIA ANJELINA (Universitas Katolik Widya Mandala Surabaya, 2012)
Going concern audit opinion or reasonable opinion without exception with explanatory paragraphs is one of the five audit opinion expressed in the auditor’s report. Going concern opinion is the opinion which suggests that the existence of reasonable doubt on the continuity of enterprises company auditors and the exixtence of opportunities for companies to bankruptcy. Conditions for companies that suffered losses are repeated and the inability of the company to meet short-term obligations may give rise to uncertainty with respect to it’s business continuity company. The company is likely to get going concern audit opinion because of some condition as follows: quality audit, financial condition of the company, the audit opinion in previous years, and the growth of the company. An independent and competent auditors have high quality. Financial condition of the company, the audit opinion in previous years, and the company’s growth dependns on the company’s ability in running his business.